Effect of powder properties on discharge characteristics of cohesive carbonaceous fuel powders from a top discharge blow tank at high pressure. Issue 11 (2nd November 2018) - Guiling, Xu; Ping, Lu; Cai, Liang; Pan, Xu; Liu, Shen; Daoyin, Liu; Xiaoping, Chen
Abstract: Discharge experiments of two cohesive carbonaceous fuel powders (anthracite coal and petroleum coke) were carried out in a top discharge blow tank experimental system with design pressure up to 6.4 MPa. The effects of powder properties (particle size and powder category) on the discharge characteristics (including solid discharge rate, solids loading ratio, and discharge stability) from the top discharge blow tank at high pressure were investigated. Meanwhile, shear tests with a ShearTrac II shear tester were performed to investigate the flowability of these two cohesive powders. The results indicate that there exists a near-linear relationship between major consolidation stress and flow function ( FF ). As particle size decreases, the values of FF decrease and powder flowability becomes worse. However, as particle size decreases, the particle suspension velocity decreases correspondingly, and the gas permeability becomes worse and gas maintain ability becomes better, which contribute to higher solid discharge rate and better discharge stability, whereas solids loading ratio may have opposite variation tendency. Compared to petroleum coke with similar particle size, anthracite coal has better flowability and can obtain higher solid discharge rate and solids loading ratio, as well as better discharge stability. During the discharge processes of petroleum coke, it was found that as the number of discharge experiment increases, the discharge stability decreases correspondingly. After petroleum coke being discharged continuously for 4–6 times, the discharge process could not start again, adhesion phenomena of petroleum coke to the wall of conveying pipelines could be observed.